Leukocyte Trafficking and Regulation of Murine Hematopoietic Stem Cells and Their Niches - Lucas, Daniel (Frontiers in Immunology, 2019)
Hematopoietic stem cells (HSC) are the most powerful type of adult stem cell found in the body. HSC are multipotent and capable of giving rise to all other types of hematopoietic cells found in the organism. A single HSC is capable of regenerating a functional hematopoietic system when transplanted into a recipient. HSC reside in the bone marrow in specific multicellular structures called niches. These niches are indispensable for maintaining and regulating HSC numbers and function. It has become increasingly clearer that HSC and their niches can also be regulated by migrating leukocytes. Here we will discuss the different components of bone marrow niches and how HSC and their niches are regulated by different types of leukocytes that traffic between the periphery and the niche.